Change in caregivers’ attitudes and use of corporal punishment following a legal ban: a multi-country longitudinal comparison - Peña Alampay, Liane (Child maltreatment, 2022)
We examined whether a policy banning corporal punishment enacted in Kenya in 2010 is associated with changes in Kenyan caregivers? use of corporal punishment and beliefs in its effectiveness and normativeness, and compared to caregivers in six countries without bans in the same period. Using a longitudinal study with six waves of panel data (2008?2016), mothers (N = 1086) in Colombia, Italy, Jordan, Kenya, Philippines, Thailand, and United States reported household use of corporal punishment and beliefs about its effectiveness and normativeness. Random intercept models and multi-group piecewise growth curve models indicated that the proportion of corporal punishment behaviors used by the Kenyan caregivers decreased post-ban at a significantly different rate compared to the caregivers in other countries in the same period. Beliefs of effectiveness of corporal punishment were declining among the caregivers in all sites, whereas the Kenyan mothers reported increasing perceptions of normativeness of corporal punishment post-ban, different from the other sites. While other contributing factors cannot be ruled out, our natural experiment suggests that corporal punishment decreased after a national ban, a shift that was not evident in sites without bans in the same period.